Prefiltering-Based Interference Suppression for Time-Hopping Multiuser UWB Communications over MISO Channel. (14th July 2009) - Wu, Wei-Chiang
Abstract : This paper proposes a prefiltering-based scheme for pulsed ultra-wideband (UWB) system by shifting the signal processing needs from the receiver at the radio terminal (RT) to the transmitter at the fixed access point (AP) where power and computational resources are plentiful. We exploit antenna array in the transmitter of AP and take advantage of the spatial and temporal diversities to mitigate the multiuser interference (MUI) as well as preequalize the channel impulse response (CIR) of a time-hopping (TH) multiple access UWB communication system. Three prefiltering schemes are developed to meet different criteria. A simple correlation receiver is proposed at the RT to combine the desired signal stemmed from all the transmitting antennas. The performances under different scenarios are extensively evaluated over multiple-input single-output (MISO) channels.